(untitled) (Research, Society and Development, 2021)
Cassava is one of the most traditional agricultural crops, it has socioeconomic relevance and it is cultivated efficiently in all regions of Brazil. The aim of this study was to characterize 71 cassava landraces, grown in the north of Mato Grosso state, Brazil, through morpho-agronomic descriptors, as well as to highlight landraces with desirable characteristics for commercial cultivation and agro-industrial processing. Thirty-one qualitative and eight quantitative descriptors were used. The data were analyzed with the aid of Excel software and the Genes program. Based on qualitative data, we observed phenotypic variability among the landraces and the formation of ten genetic groups by the UPGMA method. All landraces have roots with more than one characteristic desirable by consumers and, therefore, of agronomic and commercial interest. Through the quantitative data it was possible to form eight distinct groups. The landraces LCA09, MTA02 and MTA05 were the most dissimilar. The descriptors average length of the root (65.70%) and length of the petiole (14.44%) were the ones that most contributed to the genetic diversity among the landraces. The joint analysis of the data gathered the landraces into nine genetic groups, without duplication of material. We conclude that the cassava landraces cultivated by family farmers in Mato Grosso state have genetic diversity related to the morpho-agronomic descriptors. They have desirable characteristics for consumers, have the potential for commercial crops and agro-industrial processing, and can be useful as progenitors in breeding programs with the species.